Dietary weight-loss interventions for the management of obesity in older adults - Goisser, Sabine; Kiesswetter, Eva; Schöne, Daniel; Torbahn, Gabriel; Bauer, Jürgen M. (Reviews in Endocrine & Metabolic Disorders, 2020)
The obesity epidemic has reached old age in most industrialized countries, but trials elucidating the benefits and risks of weight reduction in older adults above 70 years of age with obesity remain scarce. While some findings demonstrate a reduced risk of mortality and other negative health outcomes in older individuals with overweight and mild obesity (i.e. body mass index (BMI) < 35 kg/m2), other recent research indicates that voluntary weight loss can positively affect diverse health outcomes in older individuals with overweight and obesity (BMI > 27 kg/m2), especially when combined with exercise. However, in this age group weight reduction is usually associated with a reduction of muscle mass and bone mineral density. Since uncertainty persists as to which level overweight or obesity might be tolerable (or even beneficial) for older persons, current recommendations are to consider weight reducing diets only for older persons that are obese (BMI ≥ 30 kg/m2) and have weight-related health problems. Precise treatment modalities (e.g. appropriate level of caloric restriction and indicated dietary composition, such as specific dietary patterns or optimal protein content) as well as the most effective and safest way of adding exercise are still under research. Moreover, the long-term effects of weight-reducing interventions in older individuals remain to be clarified, and dietary concepts that work for older adults who are unable or unwilling to exercise are required. In conclusion, further research is needed to elucidate which interventions are effective in reducing obesity-related health risks in older adults without causing relevant harm in this vulnerable population.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Aged; Aged; 80 and over; Diet; reducing; Obesity; Obesity management; Overweight